Non-Lethal Ionizing Radiation Promotes Aging-Like Phenotypic Changes of Human Hematopoietic Stem and Progenitor Cells in Humanized Mice. - Changshan Wang; Motohiko Oshima; Goro Sashida; Takahisa Tomioka; Nagisa Hasegawa; Makiko Mochizuki-Kashio; Yaeko Nakajima-Takagi; Yoichiro Kusunoki; Seishi Kyoizumi; Kazue Imai; Kei Nakachi; Atsushi Iwama (PLoS ONE, 2015)
Precise understanding of radiation effects is critical to develop new modalities for the prevention and treatment of radiation-induced damage. We previously reported that non-lethal doses of X-ray irradiation induce DNA damage in human hematopoietic stem and progenitor cells (HSPCs) reconstituted in NOD/Shi-scid IL2rγnull (NOG) immunodeficient mice and severely compromise their repopulating capacity. In this study, we analyzed in detail the functional changes in human HSPCs in NOG mice following non-lethal radiation. We transplanted cord blood CD34+ HSPCs into NOG mice. At 12 weeks post-transplantation, the recipients were irradiated with 0, 0.5, or 1.0 Gy. At 2 weeks post-irradiation, human CD34+ HSPCs recovered from the primary recipient mice were transplanted into secondary recipients. CD34+ HSPCs from irradiated mice showed severely impaired reconstitution capacity in the secondary recipient mice. Of interest, non-lethal radiation compromised contribution of HSPCs to the peripheral blood cells, particularly to CD19+ B lymphocytes, which resulted in myeloid-biased repopulation. Co-culture of limiting numbers of CD34+ HSPCs with stromal cells revealed that the frequency of B cell-producing CD34+ HSPCs at 2 weeks post-irradiation was reduced more than 10-fold. Furthermore, the key B-cell regulator genes such as IL-7R and EBF1 were downregulated in HSPCs upon 0.5 Gy irradiation. Given that compromised repopulating capacity and myeloid-biased differentiation are representative phenotypes of aged HSCs, our findings indicate that non-lethal ionizing radiation is one of the critical external stresses that promote aging of human HSPCs in the bone marrow niche.